Productivity problems of a garment manufacturing company in Cagayan De Oro City - Garcia, Flora Maye Custodio
This research using the qualitative case study method, focused on the productivity problems of a garment manufacturing company in Cagayan de Oro City. The problems were identified through an interview with the manager and observation made by the researcher. Survey questionnaires were also distributed to twenty of the employees using the random sampling method. These problems were classified under the five aspects of productivity, namely: (1) worker ability; (2) working condition; (3) production techniques; (4)administrative procedures; and (5) worker satisfaction. Results and interpretation of data showed that absenteeism, tardiness, disorganized shelves, emission of fumes, incorrect quality standards, and laxity of management were among the problems of the company. The assumption of the researcher was that problems regarding the five aspects of productivity are present in the company. The findings appeared to confirm the hypothesis except for the last aspect of productivity. There was no problem found regarding worker satisfaction. For the company to achieve productivity and profitability, the study inferred that it is important to have an awareness of the productivity problems being experienced by both labor and management. Therefore, to minimize this problems, if not eradicate them, the researcher arrived at the following recommendation; (1) the management should formulate strategies to motivate the employees to perform well; (2) working conditions should be improved for labor to increase work productivity; (3) the company should follow strict company procedures to maintain the quality of the products; (4) the management should implement strict policies, particularly regarding employee absenteeism; and (5) the labor and management should maintain a harmonious relationship for the betterment of the company.